Role of adrenomedullin2/ intermedin in pregnancy induced vascular and metabolic adaptation in mice - Yallampalli, Chandra; Betancourt, Ancizar; Mishra, Akansha; Pennington, Kathleen A.; Ruano, Simone Hernandez; Tacam, Moises; Chauhan, Madhu (Frontiers in Physiology, 2023)
This study was designed to assess the role of Adrenomedullin2 (ADM2) in pregnancy induced vascular and metabolic adaptation using ADM2 knockout mice (Adm2-/-). The Adm2-/- mice were successfully generated using Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) / Nuclease Cas 9 system. Current data shows that: 1) Ablation of ADM2 does not affect the gestational length of mice; 2) Adm2-/- females are fertile with no significant difference in number of pups/litter compared to Adm2+/+; 3) Total number of pups born dead or that die after birth is greater in Adm2-/- mice compared to Adm2+/+ mice (p=0.01); 4) Blood pressure in Adm2-/- mice is elevated during pregnancy compared to Adm2+/+ mice (p<0.05);5) The vascular sensitivity for CGRP and ADM mediated relaxation are unaltered in Adm2-/- mice compared to Adm2+/+ during pregnancy ; 6) The sensitivity of mesenteric artery for the contractile responses to angiotensin 2 are enhanced in Adm2-/- mice compared to Adm2+/+(p<0.05) ;7) Serum sFLT-1 levels are higher in pregnant Adm2-/- mice compared to pregnant Adm2+/+ mice (p=0.015),8) Adm2-/- mice develop glucose intolerance during pregnancy compared to their wild type littermates with elevated serum levels of Insulin and triglycerides in Adm2-/- mice compared to the wild types. Therefore, current data suggests a physiological role for ADM2 in pregnancy induced vascular and metabolic adaptations in mice.